POT LUCK: CULTURE, FOOD AND THE MARIJUANA EFFECT - Sudipto Sanyal (Soegijapranata Catholic University, 2009)
This paper is an attempt to open up discussions on marijuana as a psychoactive substance that engages with food and the act of eating in very complex and discursive ways. This study conducts numerous interviews that demonstrate that. frequently, marijuana is not the countercultural drug it is commonly supposed to be if analysed in its relations to food habits and the act of consumption. It also brings to light the surprising ways in which marijuana affects attitudes towards certain kinds of foods. thereby open up a space for a kind of psycho geographical tourism within the self.